Identification of a membrane-less compartment regulating invadosome function and motility - Kristyna Sala (Nature Portfolio, 2018)
Abstract Depletion of liprin-α1, ERC1 or LL5 scaffolds inhibits extracellular matrix degradation by invasive cells. These proteins co-accumulate near invadosomes in NIH-Src cells, identifying a novel invadosome–associated compartment distinct from the core and adhesion ring of invadosomes. Depletion of either protein perturbs the organization of invadosomes without influencing the recruitment of MT1-MMP metalloprotease. Liprin-α1 is not required for de novo formation of invadosomes after their disassembly by microtubules and Src inhibitors, while its depletion inhibits invadosome motility, thus affecting matrix degradation. Fluorescence recovery after photobleaching shows that the invadosome–associated compartment is dynamic, while correlative light immunoelectron microscopy identifies bona fide membrane–free invadosome–associated regions enriched in liprin-α1, which is virtually excluded from the invadosome core. The results indicate that liprin-α1, LL5 and ERC1 define a novel dynamic membrane-less compartment that regulates matrix degradation by affecting invadosome motility.